Impact of Chronic Kidney Disease on Outcomes of Primary PCI - Khan, Muhammad Idrees; Hameed Ullah; Khan, Naveed Ahmad; Spogmai; Ahmad, Sohail; Orakzai, Muhammad Hafeez (Indus Journal of Bioscience Research, 2024)
Objective: To assess the impact of chronic kidney disease (CKD) on outcomes, including major adverse cardiac events (MACE) and mortality, in patients undergoing primary percutaneous coronary intervention (PCI) at the Hayatabad Medical Complex, Peshawar. Methodology: A prospective cohort study was conducted from September 2022, to April 2023. A total of 250 patients were enrolled, divided into two groups: 125 patients with CKD (eGFR <60 mL/min/1.73m²) and 125 without CKD (eGFR ≥60 mL/min/1.73m²). Data on demographics, procedural success, MACE, mortality, and follow-up at one and three months were collected. Statistical analysis was performed using Chi-square tests to compare the outcomes between the two groups, with significance set at p < 0.05. Results: The CKD group had a significantly higher incidence of MACE (56 vs. 33 events, p = 0.003) and mortality (47 vs. 26 deaths, p = 0.01) compared to the Non-CKD group. Procedural success rates were similar between the groups (44.8% for CKD vs. 55.2% for Non-CKD, p = 0.16). These findings confirm CKD as a critical predictor of poor outcomes in PCI patients. Conclusion: CKD significantly increases the risks of MACE and mortality in PCI patients, despite similar procedural success rates. These results highlight the need for targeted management and follow-up strategies for CKD patients undergoing PCI in Pakistan